2023
DOI: 10.1097/aog.0000000000005465
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Doula Use on a Digital Health Platform and Birth Outcomes

Smriti Karwa,
Hannah Jahnke,
Alison Brinson
et al.

Abstract: OBJECTIVE: To examine the association between the use of virtual doula appointments on a comprehensive digital health platform and users' mode of birth and their birth experiences, among all platform users and Black platform users. METHODS: Data for this retrospective cohort study were extracted from individuals who enrolled in a comprehensive digital health platform, between January 1, 2020, and April 22, 2023. Multivariable logistic regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is noteworthy that future research could further explore the benefits of different digital technologies in improving adherence to oral iron supplementation in pregnant women ( 44 ). This investigation could include, but is not limited to, mobile applications, smart devices, remote monitoring systems, among others.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that future research could further explore the benefits of different digital technologies in improving adherence to oral iron supplementation in pregnant women ( 44 ). This investigation could include, but is not limited to, mobile applications, smart devices, remote monitoring systems, among others.…”
Section: Discussionmentioning
confidence: 99%
“…This method of support reaches more birthing families, particularly during the coronavirus disease 2019 (COVID-19) pandemic, and with the increasing number of hospital deserts in rural communities. In this month's issue of Obstetrics & Gynecology, the study by Karwa et al 4 (see page 175) addresses this shift toward more telehealth access for birthing families, including access to doula care. Karwa et al demonstrate that, “…virtual doula support on a digital health platform is associated with lower odds of cesarean birth and an improved birth experience.” This conclusion is consistent with other studies related to the association between pregnancy outcomes and the presence of doulas in birth.…”
mentioning
confidence: 99%
“…Typically, the intimacy of the client–doula relationship develops over a series of two to five visits for an average of 1.5–2 hours, depending on the birthing person's needs, as opposed to the up to 20 minutes per session in the Karwa et al study. 4 Further, the responsiveness of a doula who is present, who has cultivated an intimate relationship of care, gives families reassurance and a feeling of safety. If virtual doula sessions are conducted only with the pregnant individual, as in the Karwa et al study, the more holistic familial component of in-person doula care is lost.…”
mentioning
confidence: 99%
“…Karwa et al 1 identified a coding error in their data set that has slightly affected the way their numbers were tabulated. The key results and messages were not affected.…”
mentioning
confidence: 99%